Djurstudier, kritiska perspektiv, ”rapid ethnography” och hjältehundar - Nilsson, Bo (Kulturella Perspektiv – Svensk etnologisk tidskrift, 2018)
This article is a presentation of Critical Animal Studies (CAS), and an attempt to apply perspectives from CAS on representations of dogs in Swedish media. Central questions are how anthropocentrism permeate such representations, and what anthropocentrism means for the status of dogs (and animals) in general. The article illustrates how power is central for the relation between humans and dogs, and how the living conditions of dogs (and animals) are completely determined by human interests.